AI-Based Digital Start-up Model through MSME Innovation, Digital Marketing Capabilities, Towards Creative Economy Competitiveness - Umar Bakti; Maria Septijantini Alie; Iin Marliana (Penerbit Goodwood, 2026)
Purpose: This study aims to develop an AI-based digital start-up transformation model by examining the roles of technological literacy, student creativity, MSME innovation, and digital capability in enhancing competitiveness in Indonesia's creative economy. Research Methodology: A quantitative approach using Structural Equation Modeling (SEM) with SmartPLS was applied. Data were collected from 350 respondents, including students, MSME actors, and digital start-up entrepreneurs, to evaluate the relationships between key constructs. Results: The results show that technological literacy, student creativity, and MSME innovation have positive and significant effects on creative economy competitiveness. Digital capability serves as a strategic enabler that integrates digital resources and processes to improve productivity and innovation. Significant path coefficients were found for all proposed relationships, with technology literacy having the strongest effect on competitiveness. Conclusions: AI-based digital transformation plays a strategic role in strengthening the innovation ecosystem, improving operational efficiency, and enhancing competitive advantages in Indonesia’s creative economy sector. The integration of literacy, creativity, innovation, and digital capabilities forms a sustainable competitive framework. Limitations: This study is limited to the Indonesian creative economy, which may restrict its generalizability to other countries. Additionally, the cross-sectional design limited our ability to capture long-term transformation dynamics. Contributions: This study makes a significant theoretical contribution to the digital transformation and competitive advantage literature by integrating perspectives on technology literacy, creativity, and innovation in AI-based digital startups. It advances understanding of how these elements drive competitive advantage in the creative economy.